Strategies to evaluate potential effector function of glycan variants: a case study of ordesekimab (AMG 714 or PRV-015). Issue 1 (31st December 2022) - Wei, Yu-Ling; Wegesser, Teresa; Kuhns, Scott; Werner, Jonathan; Lebrec, Hervé; Wang, Xiaoting
Abstract: The potential for effector functions of therapeutic antibodies, including antibody-dependent cell-mediated cytotoxicity (ADCC), is a biological activity of interest for characterization, regardless of if ADCC is an intended primary pharmacological effect. The composition of the conserved antibody Fc glycan can vary as a function of post-translational processing which may affect the binding affinity to Fc receptors, leading to a change of effector activity. Ordesekimab (AMG 714 or PRV-015), a fully human immunoglobulin G1 -kappa anti-interleukin (IL)-15 monoclonal antibody, is in clinical development for celiac disease. The binding of ordesekimab to IL-15 inhibits the interaction of IL-15 with the IL-2Rβ and common γ chain of the IL-15 receptor complex, but not with the IL-15Rα chain. Therefore, the simultaneous binding of ordesekimab to the Fcγ receptor (R) IIIα expressed on natural killer (NK) cells and to the IL-15/IL-15Rα complex on cells such as monocytes may theoretically enable ADCC toward the IL-15Rα-expressing cells. The high mannose (HM) levels on the Fc glycan were found to vary in different lots of ordesekimab resulting from refinements to the manufacturing process, and the impact on ordesekimab-mediated ADCC activity was evaluated in in vivo and in vitro studies. A review of nonclinical and clinical data found no evidence of ordesekimab-induced depletion of monocytes, or cytotoxicity in organs with wide IL-15Rα expression, suggesting a lack of in vivo ADCC activity. In addition, in vitro peripheral blood mononuclear cells-based ADCC assay did not reveal any cytolytic effect of ordesekimab with various levels of HM content when cocultured with recombinant human IL-15. Taken together, these data demonstrate that ADCC is not a potential liability for ordesekimab and does not contribute to the reduction of IL-15-mediated inflammation, the intended pharmacological effect.